Adaptive Approaches to Tax Enforcement Amid the Emerging Challenges of the Digital Economy - Piki Rohmatuloh; Mochamad Rif'at Denasetya; Muhammad Azaria Kanigara Persada; Nurulloh Misbahul Ma'ruf; Novandio Satria Ramadhan; Nandang Najmudin (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Tax law enforcement in the digital economy era has become a major challenge for governments in ensuring taxpayer compliance amid technological advancements and cross-border business models. This study aims to analyze adaptive strategies for tax law enforcement to remain relevant in responding to digital transformation. The research uses a qualitative literature study approach, referring to Soerjono Soekanto’s theory of law enforcement, Everett Rogers’ diffusion of innovation theory, and Lawrence M. Friedman’s legal system framework. The findings indicate that the effectiveness of tax law enforcement is highly influenced by regulatory readiness, the quality of human resources, and the utilization of information technology such as big data and artificial intelligence in monitoring. The discussion emphasizes the need for inter-agency synergy and digital literacy for taxpayers to prevent tax evasion. The conclusion highlights the importance of adaptive strategies focused on collaboration, technological innovation, and fiscal justice to establish a transparent and sustainable tax system.